The new secondary education curriculum (NSEC) and the 2002 secondary education curriculum as perceived by teachers - Ubaldo, Gladys Glimada (Animo Repository, 2002)
This study was conducted in view of the recent restructuring of the secondary education curriculum. The researcher conducted a survey of the perception of the secondary school teachers towards the New secondary Education Curriculum (NSEC) and the 2002 Secondary Education Curriculum. A comparison of the teachers' beliefs, ideas and preferences regarding these curriculum was also done. A survey instrument on perception was developed and used for this purpose. The respondents were secondary school teachers of the Juan G. Macaraeg National High School in Binalonan, Pangasinan. The ratings that the respondents gave were tallied and the respective mean and standard deviation of each statement were computed. The results were interpreted using a scale. The results indicated that regardless of the number of years in the teaching profession, age and gender, the teachers gave a greater preference to the 2002 Secondary Education Curriculum over the New Secondary Education Curriculum. This curriculum's greatest feature as far as the teachers are concerned is the number of subjects/learning areas that if offers. The teachers think that the NSEC is an overcrowded curriculum. The researcher recommends that further researches regarding the perception of the teachers towards a key issue or a key trend in education be conducted and that a follow-up study on teachers' perception toward the 2002 SEC be conducted a year after the implementation.